2013
DOI: 10.1093/nar/gkt1260
|View full text |Cite
|
Sign up to set email alerts
|

TDP1 deficiency sensitizes human cells to base damage via distinct topoisomerase I and PARP mechanisms with potential applications for cancer therapy

Abstract: Base damage and topoisomerase I (Top1)-linked DNA breaks are abundant forms of endogenous DNA breakage, contributing to hereditary ataxia and underlying the cytotoxicity of a wide range of anti-cancer agents. Despite their frequency, the overlapping mechanisms that repair these forms of DNA breakage are largely unknown. Here, we report that depletion of Tyrosyl DNA phosphodiesterase 1 (TDP1) sensitizes human cells to alkylation damage and the additional depletion of apurinic/apyrimidinic endonuclease I (APE1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 45 publications
4
57
0
Order By: Relevance
“…The nervous system coordinates the defenses of the whole body to endogenous and exogenous insults by modulating the activities of neuroendocrine pathways and the autonomic nervous system (53). Hydrolysis of the 3′-terminal glycolate-DNA phosphodiester by TDP1 repairs oxidative damage (2,4,5,15,21). Restoration of the lifespan of TDP1 mutant females by expression of TDP1 with nrv2-Gal4 in the central nervous system suggests that resistance to oxidative stress in the nervous system is a prerequisite for normal lifespan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nervous system coordinates the defenses of the whole body to endogenous and exogenous insults by modulating the activities of neuroendocrine pathways and the autonomic nervous system (53). Hydrolysis of the 3′-terminal glycolate-DNA phosphodiester by TDP1 repairs oxidative damage (2,4,5,15,21). Restoration of the lifespan of TDP1 mutant females by expression of TDP1 with nrv2-Gal4 in the central nervous system suggests that resistance to oxidative stress in the nervous system is a prerequisite for normal lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…aging | neuroscience | DNA repair | topoisomerase | fly D NA repair is indispensable to maintaining genomic integrity against the various endogenous and exogenous agents and enzymes that react with DNA, including reactive oxygen species (1-3), base-damaging agents (4,5), and chain-terminating nucleosides (6), which yield nonligatable DNA ends. In addition, topoisomerase I (Top1) (7-9) is capable of generating strand breaks with protein-blocked 3′ ends.…”
mentioning
confidence: 99%
“…13,14 Furthermore, camptothecin and etoposide cause less DNA damages in cells with heightened TDP1 expression. [15][16][17][18] In addition, TDP1 activity suppression makes tumor cells hypersensitive to the anticancer agent temozolomide (purine methylation), 19 methyl methanesulfonate (AP-sites generation), bleomycin (single/double strand breaks with 3 0 -phosphoglycolates), H 2 O 2 and ionizing radiation (breaks and other lesion types). 20 For all of these DNA damaging agents it can be assumed that TDP1 is involved in DNA repair.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in vitro studies demonstrated trapping of TOP1 by nicks or DNA secondary structures 28 . More recent in vivo work has shown that ionizing radiation and chemotherapies such as alkylating agents can also generate PDBs, at least a subset of which are repaired by activities that liberate TOP1 from DNA termini [29][30][31] .…”
Section: Targeting Topoisomerases In Cancer Therapymentioning
confidence: 99%